SUPPLEMENTATION OF RICE STRA W WITH VARIOUS NITROGEN SOURCES TO IMPROVE THE YIELD OF PLEUROTUS SAJOR-CAJU - KAUSAR , TASNlM; IQBAL , S. H. (Biological Sciences - PJSIR, 2022)
Pleura/us sajar-caju was cultivated on rice straw. Supplementation of rice straw with different pulse (2% w/w), inorganic and organic sources (0.92% Nitrogen level) increased the yield from 72.3 to 83.5% maximum being on addition of 'Lobia' (Vigna cajang) followed by corn gluten meal (79.7%). Supplementation or rice straw with gram, black gram, red gram and french beans showed almost non-significant stimulatory effect whereas ammonium sulphate, ammonium nitrate, urea and mustard seed meal retard the growth of P. sajar-caju.